The invasive giant African snail Lissachatina fulica as natural intermediate host of Aelurostrongylus abstrusus, Angiostrongylus vasorum, Troglostrongylus brevior, and Crenosoma vulpis in Colombia. - Felipe Penagos-Tabares; Malin K Lange; Juan Vélez; Jörg Hirzmann; Jesed Gutiérrez-Arboleda; Anja Taubert; Carlos Hermosilla; Jenny J Chaparro Gutiérrez (Public Library of Science (PLoS), 2019)
Background Several metastrongyloid lungworms are unreported pathogens in Colombia. Angiostrongylus vasorum and Crenosoma vulpis target the cardiopulmonary system of domestic and wild canids. Aelurostrongylus abstrusus and Troglostrongylus brevior infect felids and considering that six wild felid species exist in Colombia, knowledge of feline lungworm infections is important for their conservation. The zoonotic metastrongyloids Angiostrongylus costaricensis and Angiostrongylus cantonensis can cause severe gastrointestinal and neurological diseases. Angiostrongylus costaricensis has been reported in Colombia, while Ang. cantonensis is present in neighbouring countries. Research on the epidemiology of metastrongyloids in Colombia and South America more broadly requires evaluating the role that gastropods play as intermediate hosts in their life cycles. This study assessed the prevalence of metastrongyloid larvae in populations of the invasive giant African snail, Lissachatina fulica, in Colombia. Methodology/principal findings A total of 609 Lissachantina fulica were collected from 6 Colombian municipalities. The snails were then cryo-euthanized, artificially digested and the sediments examined microscopically for the presence of metastrongyloid larvae. Based on morphological characteristics 53.3% (56/107) of the snails from Puerto Leguízamo (Department of Putumayo) were infected with Ael. abstrusus larvae, 8.4% (9/107) with Ang. vasorum larvae, 6.5% (7/107) with T. brevior larvae and 5.6% (6/107) with C. vulpis larvae, being the region with highest prevalences of the four species. Snails from Andes (Department of Antioquia) and Tulúa (Department of Valle del Cauca) were positive for Ang. vasorum larvae with a prevalence of 4.6 (11/238) and 6.3% (4/64), respectively. Species identifications were confirmed by PCR and sequencing. Conclusions/significance This epidemiological survey reports for first time the presence of Ael. abstrusus, T. brevior, C. vulpis and Ang. vasorum in L. fulica in a number of regions of Colombia.